Frequency Of Depression Among Adolescents With Asthma: A Prospective Analysis - Muhammad Nouman; Zaheer Hussain Memon; Muhammad Khalid Nizamani; Shaista Ahmed; Tasneem Kousar; Hira Saeed Khan (KARACHI MEDICAL AND DENTAL COLLEGE, 2024)
Objective: To evaluate the frequency of depression among adolescents aged 13 to 19 years who visit medicine outpatient departments (OPD) for asthma. Methods: This prospective, cross-sectional study was conducted in Outpatient Departments of Medicine, of Indus Medical College TM Khan. All the cases between the ages of 13 and 19 who visited the medicine departments and have been diagnosed as patients of asthma for at least one year were included. Patients with a history of major life events, such as the death of a family member or any other relevant severe trauma within the past 3 months, patients already on antidepressant treatment for the past 3 months, those with other diseases such as diabetes, tuberculosis, or epilepsy, and those with a history of substance abuse or dependence were not incorporated. Depression diagnosis was based on DSM-IV criteria, requiring the presence of at least five symptoms during the same two-week period, representing a change from previous functioning. Data was entered and analyzed using SPSS version 26. Results: A total of 262 asthma patients were included, with a mean age of 16.63+4.8 years and aver- age duration of asthma was 5.6 years. Among the participants, 169 (64.5%) were female. The family history of asthma was reported in 30 (11.4%) of the cases. Overall frequency of depression was found to be at 14.1% (n=37). In terms of gender, a significant difference was observed, with a higher occurrence of depression in males (78.4%) and patients with poor and middle socio-economic status (SES) (p = 0.001). Higher rates of depression were also among those who were illiterate compared to educated patients (p = 0.001). Conclusion: Study revealed that depression is common among teenagers with asthma. Both asthma and depression are highly prevalent in teenagers as well as in adults, and emerging evidence indicates that these conditions often occur together